ĐÁNH GIÁ HIỆU QUẢ CỦA LIỆU PHÁP OXY CAO ÁP TRONG CẢI THIỆN NHẬN THỨC Ở BỆNH NHÂN ALZHEIMER MỨC ĐỘ NHẸ VÀ TRUNG BÌNH - Nguyễn, Huy Hoàng; Trần, Danh Tiến Thịnh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
EVALUATION OF THE EFFECTIVENESS OF HYPERBARIC OXYGEN THERAPY IN IMPROVING COGNITIVE FUNCTION IN PATIENTS WITH MILD AND MODERATE ALZHEIMER’S DISEASEObjective: To evaluate the effectiveness of hyperbaric oxygen therapy (HBOT) in improving cognitive function in patients with mild and moderate Alzheimer’s disease.Subjects and Methods: A randomized controlled clinical trial was conducted on 90 patients with mild to moderate Alzheimer’s disease, including 60 patients in the HBOT group and 30 patients in the control group who received Tanakan 40 mg. Cognitive function was assessed using the MMSE score before treatment and after 20, 40 and 60 sessions. The HBOT group underwent therapy in a hyperbaric oxygen chamber at a pressure of 2.0 ATA, for 60-70 minutes per session, with 5 sessions per week.Results: The study results indicate that the hyperbaric oxygen therapy group showed significant improvement in MMSE scores after 20 sessions of treatment and with optimal effects archieved after at least 40 sessions. The average MMSE score increased from 19.0 to 22.4 points. The proportion of patients classified at the mild stage increased from 48.3% to 82.5%, and 2.5% reached a normal cognitive level. In contrast, the Tanakan 40 mg group showed no statistically significant changes in MMSE scores (p>0.05) after 60 days of treatment.Conclusion: Hyperbaric oxygen therapy demonstrates superior effectiveness in improving cognitive function in patients with mild and moderate Alzheimer’s disease, particularly after 40 and 60 sessions of treatment. This method shows promise as a potential intervention for Alzheimer’s disease.